2019
DOI: 10.3390/min9030140
|View full text |Cite
|
Sign up to set email alerts
|

Scrubbing and Inhibiting Coagulation Effect on the Purification of Natural Powder Quartz

Abstract: The low removal efficiency of fine clay impurities in natural powder quartz (NPQ) is the main problem that affects the practical utilization of this natural resource. In this work, detailed characterizations of NPQ and clay impurities in NPQ were analyzed by SEM-EDS, mineral liberation analysis (MLA) and impurities distribution analysis. A combined physical purification process, including sieving, scrubbing and centrifugation, was applied to remove the clay impurities. It was observed that the fine clay impuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Du et al [14] also contributed to this Special Issue by discussing scrubbing and the inhibiting coagulation effect on the purification of quartz particles. The low removal efficiency of fine clay impurities in natural quartz is the main problem affecting the practical usage of this resource.…”
Section: The Special Issuementioning
confidence: 99%
“…Du et al [14] also contributed to this Special Issue by discussing scrubbing and the inhibiting coagulation effect on the purification of quartz particles. The low removal efficiency of fine clay impurities in natural quartz is the main problem affecting the practical usage of this resource.…”
Section: The Special Issuementioning
confidence: 99%
“…The genesis of quartz deposits is influenced by multifarious factors, culminating in substantial disparities in quartz concentration, impurity mineral typologies, and their respective levels across geographies. Typically, indigenous quartz deposits harbor a plethora of impurity minerals, encompassing iron minerals (notably hematite and limonite), rutile, calcite, mica, feldspar varieties (including potassium and sodium feldspar), and clay minerals, among others [3]. During geotectonic processes, quartz crystals, with entrapped solid and fluid inclusions of metallic impurities, gases, and aqueous molecules, significantly enhance the impurity quotient of quartz silicates [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…(2) Pegmatite Quartz: derived from pegmatites, these quartz crystals can be exceptionally pure, often used for high-end electronic and optical applications [10][11][12][13]. (3) Hydrothermal Vein Quartz: formed from hydrothermal fluids, this type includes vein quartz with high SiO2 content but can have numerous gas-liquid inclusions and associated minerals like pyrite, hematite, mica, and feldspar [14]. (4) Metamorphic Quartz: includes quartzites and metamorphogenic mobilizates formed under high-pressure and high-temperature conditions, often resulting in high-density, hard quartz with some impurities like iron minerals, feldspars, and clay minerals [15].…”
Section: Introductionmentioning
confidence: 99%
“…The attrition scrubbing process was applied to remove clay mineral that contained Al 2 O 3 and Fe 2 O 3 from quartz including silica sand (Aguiree-Villafana & Leal-Gonzalez, 1994;Du et al, 2019;Raghavan et al, 2006). The parameters that were studied are retention time and solid percentage.…”
Section: The Stain Removal From the Mineral Surfaces Using Attrition ...mentioning
confidence: 99%
“…The parameters that were studied are retention time and solid percentage. For retention time, Du et al (2019) treated quartz by attrition scrubbing process at retention time of 25 min. The result showed that the Al 2 O 3 and Fe 2 O 3 was decreased from 0.040% and 0.048% to 0.033% and 0.020%, respectively.…”
Section: The Stain Removal From the Mineral Surfaces Using Attrition ...mentioning
confidence: 99%